Risk‐stratified analysis of pasireotide for patients undergoing pancreatectomy. Issue 2 (30th May 2020) - Peng, June S.; Joyce, Daniel; Brady, Maureen; Groman, Adrienne; Attwood, Kristopher; Kuvshinoff, Boris; Hochwald, Steven N.; Kukar, Moshim
Abstract: Background and Objectives: Pasireotide was shown in a randomized trial to decrease the rate of postoperative pancreatic fistula (POPF). However, retrospective series from other centers have failed to confirm these results. Methods: Patients who underwent pancreatoduodenectomy or distal pancreatectomy between January 2014 and February 2019 were included. Patients treated after November 2016 routinely received pasireotide and were compared to a retrospective cohort. Multivariate analysis was performed for the outcome of clinically relevant POPF (CR‐POPF), with stratification by fistula risk score (FRS). Results: Ninety‐nine of 300 patients received pasireotide. The distribution of high, intermediate, low, and negligible risk patients by FRS was comparable ( P = .487). There were similar rates of CR‐POPF (19.2% pasireotide vs 14.9% control, P = .347) and percutaneous drainage (12.1% vs 10.0%, P = .567), with greater median number of drain days in the pasireotide group (6 vs 4 days, P < .001). Multivariate modeling for CR‐POPF showed no correlation with operation or pasireotide use. Adjustment with propensity weighted models for high (OR, 1.02, 95% CI, 0.45‐2.29) and intermediate (OR, 1.02, CI, 0.57‐1.81) risk groups showed no correlation of pasireotide with reduction in CR‐POPF. Conclusions: Pasireotide administration after pancreatectomy was not associated with a decrease in CR‐POPF, even when patients were stratified by FRS.